Lifestyle pattern underlying organic and traditional food consumption. Issue 11 (28th October 2014) - Nikolić, Aleksandra; Uzunović, Mirza; Spaho, Nermina
Abstract : Purpose: – The purpose of this paper is to set out to define lifestyle pattern framing behavior shared by traditional food products (TFP) and organic foods (OF) consumers to identify, if possible, a generic way to facilitate development of TFP and OF production in order to pave the road for more sustainable food production and consumption. Design/methodology/approach: – A convenience, non-probabilistic sample ( n =800) was designed and customer survey was conducted in December 2013 in Bosnia and Herzegovina. Exploratory factor analysis and cluster analysis were performed to identify common lifestyle pattern shaping consumption of both products' groups. Findings: – TFP and OF consumption patterns are driven by common lifestyle pattern defined by concern for welfare of all people, social equality and nature; and by consumers' belief that food is a basis of their health, while food and cooking make an important part of family life. Practical implications: – This study shows that public and private promotion/marketing policies for OF and TFP need to be designed in a way that strongly emphasizes their symbolic meaning that elicits in consumers feeling of belonging to both local community and their family, and at the same time highlights the level of social responsibility of their producers. In addition, this study contributes to the body of knowledge in this area. Originality/value: – No similar study has been done to date that was focussed on identifying common combination of lifestyle factors that frame and drive customers' tendency to purchase either TFP or OF products. This study offers a unique and valuable insight into topics and values around which a generic public or private promotional strategy for the two product groups would evolve, and which will decide effectiveness of any such strategy.